Les dérives d’un système : Le scandale de Clairvaux en 1847 - Dominique Fey; Lydie Herbelot (Criminocorpus)
Starting from June 13th, 1847, a local republican newspaper Le Propagateur de l’Aube publishes a series of articles which are going to make speak about them. They concern the prison of Clairvaux and its functioning at least shady. The subject has nothing trivial because the daily paper so underlines practices and reality which rarely go beyond the prison surrounding walls. Actually, it is question of hungry, wild prisoners there, who would die by hundreds since 1845, that is shortly after the installation of the new entrepreneurs.It is doubtless the first time that representatives of the general company of the services in charge of the maintenance and the work of prisoners in prisons, are implicated so clearly. National newspapers, then members of parliament of the National Assembly having taken over, the affair is going to give rise to an unprecedented trial. Even if its scale and its conclusions remain on the whole limited, it will however be the opportunity to put in full light unworthy actions, so far away from the major principles of the philanthropists regarding prisons.